IDENTIFIKASI DAMPAK PERUBAHAN IKLIM TERHADAP SERI DATA HUJAN DI PULAU JAWA - Wanny Kristyanti Adidarma (JURNAL SUMBER DAYA AIR, 2009)
The identification of climate change impacts on rainfall (annual, seasonal and monsoon rainfall) wasstudied using hundreds of rainfall data ranging from 1916-2006. The existence of trend in annual andseasonal rainfall series was detected by Statistical Test, namely Mann-Kendall and the Difference of TwoPopulations in monsoon series using Mann-Whitney.The results of the test showed that annual and seasonal rainfalls in most of the studied area had decreasedwhere others had increased. The monsoon rainfall showed a significant difference in frequency distributionparticularly in the months March-April-May (MAM) and December-January-February (DJF).